Harvest index is a key trait for screening drought-tolerant potato genotypes (Solanum tuberosum) - Lozano-Isla, F.; Farfan-Vignolo, E.R.; Gutierrez, R.; Blas, R.; Awais, K. (2024)
Drought stress is a significant constraint that affects the yield of almost all major crops. Its impact is expected to worsen due to global climate change and human population expansion. Potato (Solanum tuberosum L.) is the third most important food crop worldwide, but it is highly susceptible to drought stress. In order to understand the effects of drought stress on yield and identify traits for selecting drought-tolerant potato genotypes, we evaluated the response of a range of agronomic and physiological traits in 15 potato genotypes under well-watered (WW) and water deficit (WD) conditions. The harvest index (HI) was found to have a high plot-based heritability (0.98), indicating that it can be used for the indirect selection of drought-tolerant genotypes. In contrast, SPAD was sensitive to detecting early drought stress in potatoes. Drought-tolerant genotypes, including CIP392797.22 (UNICA), CIP397077.16, CIP398190.89, CIP398208.219, and CIP398208.620, were able to allocate limited water towards tuber production rather than biomass. These genotypes showed high tuber production under WW conditions and increased photosynthetic activity and water use efficiency under WD conditions.